Tuberculous Meningitis: The Important Role of Imaging - Pereira Lemos, A (2022)
Tuberculous meningitis is the most severe form of tuberculosis, and the diagnosis continues to be challenging for clinicians. Indeed, many cases of tuberculous meningitis cannot be confirmed based on clinical findings, and laboratory techniques are largely insensitive or slow. Clinical presentation can be nonspecific and suggest alternative conditions. The difficulty in diagnosis often leads to a delay in treatment and subsequent morbidity and mortality. We present the case of a 4-year-old Indian girl with meningitis that presented neurological deterioration while taking antibiotics. The epidemiological history and neuroimaging findings of incipient hydrocephalus, infarcts, and probable tuberculomas were essential to evoking the diagnosis of tuberculous meningitis. Diagnosis of tuberculous meningitis is difficult mainly in these rare cases with acute presentation that clinically present similarly to other forms of meningitis. The recognition of this entity involves a high index of suspicion based on the previous referred findings and is essential to prevent morbidity and mortality.